Pengetahuan Pasangan Usia Subur Tentang Suntik Depo Progestin - Indryani Indry Idris; Hasliana Haslan (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Fertile age couples are very easy to get offspring and therefore need to regulate fertility by having good knowledge in choosing contraception. The purpose of this study was to determine the study of the level of knowledge of fertile age couples about the injection method of progestin depo in the working area of ​​the Ulaweng Community Health Center. This research was conducted by a cross-sectional study, which was carried out in pus using injections of Depo progestin as many as 30 people. Data collection using a questionnaire with progestin depo injection questions. In this study, a univariate test was conducted. The results of the study where based on knowledge about the benefits of contraception Depo Progestin good knowledge 24 people (80%) and less knowledge 6 people (20%), knowledge about the schedule of good knowledge giving 20 people (67%) and less knowledge 10 people (33%) knowledge about the side effects of good knowledge 25 people (83%) and less knowledge 5 people (17%) knowledge about the indications of contraceptive use Depo progestin good knowledge still less 14 people (46%) and less knowledge as many as 16 people (54%) regarding contraindications to the knowledge of both 17 people (57%) and knowledge of less 13 people (43%). The conclusion in this study is that good EFA knowledge about benefits, schedule of side effects and contraindications regarding contraceptive injection of depo progestin, and lack of knowledge about the indications for Depo progestin injection.